Redox conditions and authigenic mineralization related to cold seeps in central Guaymas Basin, Gulf of California. (August 2018) - Núñez-Useche, Fernando; Canet, Carles; Liebetrau, Volker; Puig, Teresa Pi; Ponciano, Alejandro Cristin; Alfonso, Pura; Berndt, Christian; Hensen, Christian; Mortera-Gutierrez, Carlos; Rodríguez-Díaz, Augusto Antonio
Abstract: Authigenic carbonate crusts, surface muds and bivalve shell fragments have been recovered from inactive and active recently discovered cold seep sites in central Guaymas Basin. In this study, for first time, redox conditions and fluid sources involved in mineral precipitation were investigated by analyzing the mineralogy and textures of surface samples, along with skeletal contents, and C, O and S isotopes variations. The δ 13 C values of aragonitic bivalve shells and non-skeletal carbonate from some surface muds (1‰ to −3.7‰ V-PDB) suggest that carbonate precipitated from ambient dissolved inorganic carbon, whereas fibrous aragonite cement and non-skeletal carbonate from other sites are highly depleted in 13 C (down to −47.6‰ V-PDB), suggesting formation via anaerobic oxidation of methane, characteristic of methane seepage environments. δ 18 O in most of the carbonates varies from +1.4‰ to +3.2‰ V-PDB, indicating that they formed from slightly modified seawater. Some non-skeletal carbonate grains from surface muds have lower δ 18 O values (−12.5‰ to −8.2‰ V-PDB) reflecting the influence of 18 O-depleted pore water. Size distribution of pyrite framboids (mean value: 3.1 μm) scattered within diatomaceous sinter suggests formation from anoxic-sulfidic bottom waters. δ 34 S in pyrite is of −0.3‰ V-CDT compared to +46.6‰ V-CDT in barite, thus implying a fluid sulfate−sulfide fractionation of 21.3‰ that argues in favor of microbial sulfate reduction as the processes that mediated pyrite framboid formation, in a semi-closed system. Barite formation occurred through the mixing of reducing and Ba-rich seep fluids with a 34 S-enriched sulfate pool that resulted from microbial sulfate reduction in a semi-closed system. The chemical composition of aragonite cement, barite and pyrite suggest mineral precipitation from modified seawater. Taken together, our data suggest that mineralization at the studied seep sites is controlled by the mixing of seawater with minor amounts of hydrothermal fluids, and oxygen-depleted conditions favoring anaerobic microbial processes. Highlights: In cold seeps of Guaymas Basin, aragonite, barite and pyrite precipitated from modified seawater. Aragonite is highly depleted in 13 C suggesting formation via anaerobic oxidation of methane. Barite formed through mixing of reducing, Ba-rich seep fluids with a 34 S-rich sulfate pool. Pyrite framboids formed under anoxic-sulfidic water via microbial sulfate reduction.